Sulfur-doped metatitanic acid / graphene oxide two-dimensional composite lithium ion sieve and preparation method thereof
By loading sulfur-doped Li4Ti5O12 nanoparticles onto graphene oxide to form the H4Ti5O12-xSx@GO structure, the problem of insufficient adsorption capacity and selectivity of titanium-based lithium ion sieves is solved, and efficient lithium ion adsorption and selectivity are improved.
Patent Information
- Application Number
- CN202511386828.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-26
- Publication Date
- 2025-11-07
AI Technical Summary
Existing titanium-based lithium ion sieves have limited adsorption capacity, high titanium dissolution rate, and poor selectivity, which restricts their industrial application.
A two-dimensional composite lithium-ion sieve, consisting of sulfur-doped metatitanic acid/graphene oxide, is employed. By loading sulfur-doped spinel-type Li4Ti5O12 nanoparticles onto graphene oxide, an H4Ti5O12-xSx@GO structure is formed, thereby improving the specific surface area and lithium-ion selectivity.
It significantly improves the adsorption capacity and selectivity of lithium-ion sieves, reduces titanium dissolution rate, and enhances the hydrophilicity and ion diffusion kinetics of the material, showing good prospects for industrial application.
Smart Images

Figure CN120900585A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of ion sieve adsorption, and relates to a lithium ion sieve, in particular to a composite lithium ion sieve and an in-situ preparation method thereof, which is applied to the adsorption extraction of liquid lithium resources. BACKGROUND
[0002] Lithium is known as the "energy metal" of the 21st century, and has an irreplaceable strategic position in the fields of new energy vehicles, energy storage systems, and portable electronic devices. Global lithium resources mainly exist in salt lake brine. However, due to the low concentration of lithium ions and the high magnesium-lithium ratio in the brine, efficient and high-selectivity extraction of lithium has become a formidable challenge (Energies 18 (2025) 3146).
[0003] Among the numerous adsorption materials, titanium-based lithium ion sieves (LTO, such as layered H2TiO3 and spinel-type H4Ti5O 12 ) are considered as one of the most promising lithium-selective adsorbents due to their high selectivity for lithium ions, low titanium dissolution rate, and good cycle stability. However, the widespread application of H4Ti5O 12 still faces several technical bottlenecks: although its theoretical adsorption capacity is as high as 60.84 mg·g -1 , the actual adsorption capacity is much lower than this value. The reasons include the following aspects: first, lithium titanate materials synthesized by traditional solid-phase methods usually have large particles, resulting in small specific surface area, insufficient exposure of active sites, and thus slow adsorption rate; second, the structural stability of the material during acid elution of lithium still needs to be improved, and the dissolution of titanium ions seriously restricts its cycle service life; finally, in the complex actual brine system, Na + , K + , Mg 2+ , Ca 2+ and other coexisting cations will compete for adsorption sites, significantly reducing the selectivity of the material for lithium. Therefore, in view of the above problems of H4Ti5O 12 adsorbent, effective structural optimization and performance modification are needed to greatly improve its actual adsorption performance and cycle stability.
[0004] Graphene oxide is a product of graphite powder after chemical oxidation and exfoliation, and graphene oxide is a single atomic layer, which can be expanded to tens of microns in lateral size at any time. Therefore, its structure spans the typical scale of general chemistry and material science (Chemical society reviews 39 (2010) 228). Graphene oxide can be regarded as a non-traditional type of soft material, which has the characteristics of polymers, colloids, thin films, and amphiphilic molecules. Graphene oxide has been regarded as a hydrophilic substance for a long time, because it has excellent dispersibility in water. Graphene oxide can exist at the interface like a surfactant, and reduce the energy between the interfaces.
[0005] At present, the titanium-based lithium ion sieve has problems of limited adsorption capacity, high titanium dissolution rate and poor selectivity, which restricts its industrialization and application. SUMMARY
[0006] The present application aims to solve the problems of the existing titanium-based lithium ion sieve, and provides a sulfur-doped metatitanic acid / graphene oxide two-dimensional composite lithium ion sieve to improve the adsorption capacity and selectivity of lithium ion sieve, reduce the titanium dissolution rate and improve the cycle performance.
[0007] Another object of the present application is to provide a preparation method of the lithium ion sieve.
[0008] The technical scheme adopted by the present application is: a sulfur-doped metatitanic acid / graphene oxide two-dimensional composite lithium ion sieve, characterized in that the active component is a precursor Li4Ti5O 12-x S x S 12-x S x The active component H4Ti5O 12-x S x S 12-x S x @GO; wherein x=0.05-0.8.
[0009] The active component of the composite lithium ion sieve is a sulfur-doped spinel Li4Ti5O 12 S 12 The sulfur-doped spinel Li4Ti5O 12-x S xBy maintaining the spinel structure, the delithiated lithium-ion sieve can improve adsorption capacity and lithium-ion selectivity. The composite lithium-ion sieve is a two-dimensional adsorption material using graphene oxide as its supporting framework. The active component is loaded onto a single layer of graphene oxide, thereby increasing its specific surface area and improving adsorption capacity and efficiency.
[0010] Preferably, in the composite lithium-ion sieve, x = 0.1-0.5.
[0011] Furthermore, in the composite lithium-ion sieve, the active component is derived from the precursor Li4Ti5O. 12 The mass ratio of Li4Ti5O to the support is calculated. 12 : GO=1: (0.0125~0.05).
[0012] The present invention also provides the above-mentioned H4Ti5O 12-x S x The preparation method of @GO composite lithium-ion sieve includes the following steps: Graphene oxide was ultrasonically dispersed in ethanol until homogeneous, and the pH of the solution was adjusted to 2-3. Then, titanium, lithium, and sulfur sources were added and stirred to dissolve them into a mixed solution. Deionized water was added, and the resulting product was dried and calcined in a nitrogen atmosphere to obtain a precursor. The precursor was then subjected to acid leaching to remove lithium, filtered, washed, and dried to obtain H4Ti5O. 12-x S x @GO Lithium Ion Screen.
[0013] Furthermore, after the graphene oxide was ultrasonically dispersed in anhydrous ethanol, oxalic acid was added to adjust the pH of the solution.
[0014] Preferably, the titanium source is selected from inorganic or organic titanium such as tetrabutyl titanate, tetraisopropyl titanate, titanium acetate, titanium nitrate, titanium sulfate, and titanium chloride.
[0015] Preferably, the lithium source is selected from lithium acetate, lithium nitrate, lithium hydroxide, or lithium carbonate, or their hydrates.
[0016] Preferably, the sulfur source is selected from lithium sulfide, thiourea, thioacetamide, titanium disulfide, or sulfur.
[0017] Preferably, in the mixed solution, the molar ratio of titanium to lithium is equal to that of Li₄Ti₅O. 12 The stoichiometric ratio, or to compensate for the loss of Li during the preparation process, is such that lithium is slightly in excess in the mixed solution, and is calculated according to Li₄Ti₅O₂. 12 Calculation, Li4Ti5O 12 The mass ratio of :GO is 1: (0.0125~0.05).
[0018] Preferably, the molar ratio of Ti:S in the mixed solution is 5:x, x=0.05-0.8, such as x=0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.6, 0.7, 0.8, but not limited to.
[0019] Preferably, the calcination temperature is 650-850 ℃ and the calcination time is 2-5 h under N2 atmosphere.
[0020] Further, the acid solution used for acid leaching delithiation of the precursor is one or more of hydrochloric acid, sulfuric acid, phosphoric acid, oxalic acid, nitric acid, formic acid and acetic acid.
[0021] Preferably, the concentration of the acid solution for acid leaching delithiation is 0.10-0.25 mol·L -1 , and the soaking time is 12 h-36 h.
[0022] Beneficial effects: The lithium ion sieve of the present application uses two-dimensional graphene oxide (GO) as the support matrix of H4Ti5O 12 , and simultaneously performs sulfur doping to jointly construct a composite structure lithium ion sieve material. The preparation method combines sol-gel method and high-temperature solid phase method to in-situ load sulfur-doped spinel Li4Ti5O 12 nanoparticles on single-layer graphene oxide (GO) to form a Li4Ti5O 12-x S x @GO precursor, and obtain a lithium ion sieve after delithiation. The lithium ion sieve exhibits high lithium adsorption capacity, significantly reduced titanium dissolution loss rate, ultra-high hydrophilicity and excellent ion selectivity, and has good industrial application prospect.
[0023] Compared with the prior art, the lithium ion sieve of the present application has the following advantages: 1. GO is used as the loading material, and the specific surface area of H4Ti5O 12 is increased by using the single-layer structure, thereby increasing the adsorption capacity and adsorption efficiency.
[0024] 2. The abundant oxygen-containing groups (-OH, -O-, -COOH) on the surface of the carrier GO can reduce the diffusion energy barrier, accelerate the transport of electrolyte ions, reduce the irreversible reaction of surface termination, increase the chemical affinity and adsorption capacity of lithium ions of GO, and improve the selectivity of the lithium ion sieve.
[0025] 3. By partially replacing lattice oxygen with sulfur doping, the low electronegativity of sulfur introduces more free electrons, significantly improving the intrinsic electronic conductivity of the material and effectively suppressing electrode polarization. Simultaneously, sulfur doping with a larger ionic radius induces moderate lattice expansion, further widening the lithium-ion transport channels and synergistically enhancing ion diffusion kinetics.
[0026] 4. The presence of -OH groups on the GO surface enhances the H4Ti5O 12 Its hydrophilicity facilitates full contact with lithium-containing solutions, allowing H4Ti5O to... 12 The adsorption capacity is improved. Attached Figure Description
[0027] Figure 1 The Li4Ti5O prepared in Example 1 of this invention 11.7 S 0.3 @GO and H4Ti5O 11.7 S 0.3 XRD pattern of @GO; Figure 2 The Li4Ti5O prepared in Example 1 of this invention 11.7 S 0.3 @GO's SEM image; Figure 3 The H4Ti5O prepared in Example 1 of this invention 11.7 S 0.3 @GO's water contact angle diagram; Figure 4 The H4Ti5O prepared in Example 1 of this invention 11.7 S 0.3 @GO's Ti 4+ Dissolution rate and Li + Elution rate graph; Figure 5 The Li4Ti5O prepared in Examples 2-5 of this invention 12-x S x XRD pattern of @GO; Figure 6 The Li4Ti5O prepared in Examples 6-10 of this invention 12-x S x XRD pattern of @GO; Figure 7 The Li4Ti5O prepared in Examples 11-15 of this invention 12-x S x XRD pattern of @GO. Detailed Implementation
[0028] The following examples are only used to illustrate the best implementation of the present invention, and the scope of protection of the present invention is not limited to the specific implementation.
[0029] Example 1
[0030] (1) Lithium ion sieve H4Ti5O 11.7 S 0.3 Preparation of GO The GO (0.0387 g) powder was added to a beaker containing anhydrous ethanol and ultrasonically treated for 1 h. Subsequently, anhydrous oxalic acid (1.7 g, 0.019 mol) was added and stirring was continued to mix uniformly. Then, tetrabutyl titanate (5.74 g, 0.017 mol), lithium acetate dihydrate (1.41 g, 0.021 mol) and lithium sulfide (0.047 g, 0.0010 mol) were sequentially added to the mixed solution, and the Ti: S molar ratio in the reaction system was 5: 0.3. The mixture was placed in a magnetic stirrer for stirring until completely dissolved, and 1 ml of deionized water was added. The resulting product was dried in an 80 ℃ oven for 48 h, and then calcined at 750 ℃ for 3 h in a tube furnace under N2 atmosphere to obtain the precursor Li4Ti5O 11.7 S 0.3 GO. The precursor was immersed in 0.25 mol·L -1 HCl solution for 24 h to remove lithium, followed by filtration, washing and drying in a 50 ℃ oven for 12 h, and finally the product lithium ion sieve H4Ti5O 11.7 S 0.3 GO was obtained.
[0031] Quantitative Li4Ti5O 11.7 S 0.3 GO was immersed in 0.25 mol·L –1 HCl solution for 24 h to remove lithium, and the Li + elution rate and Ti 4+ solubility loss rate during the acid washing process were determined, and the calculation formula (1) is as follows: (1) Wherein, R is the mass ratio of M element in the solution to the mass of M element in the precursor; M is the element Li + or Ti 4+ to be tested; C(M) is the mass concentration of M element in the solution, mg·L -1 ; V is the volume of the solution, L; m(M) is the mass of M element in the precursor for removing lithium by acid immersion, g.
[0032] (2) Adsorption test 1 g of H4Ti5O 11.7 S0.3 @GO was placed in 1 L salt lake brine containing Li + , Na + , Ca 2+ , K + and Mg 2+ ions, pH = 8, and the saturated adsorption capacity of each ion and the adsorption selectivity of lithium ion were determined. The initial concentrations of ions in the salt lake brine were C Li+ = 73.23 mg·L -1 , C Na+ = 232.8 mg·L -1 , C Ca2+ = 169.5 mg·L -1 , C K+ = 299.3 mg·L -1 and C Mg2+ = 337.6 mg·L -1 .
[0033] The water contact angle of H4Ti5O 11.7 S 0.3 @GO and H4Ti5O 12 S 11.7 @GO was determined, as Figure 3 .
[0034] The results are shown in Table 1 of the application example.
[0035] Figure 1 The XRD images of Li4Ti5O 0.3 S 11.7 @GO and H4Ti5O 0.3 S 11.7 @GO are shown. According to the XRD image, the crystallinity thereof was calculated to be 81%. The characteristic peaks of Li4Ti5O 0.3 S 12 @GO roughly accord with the standard XRD pattern of monoclinic Li4Ti5O 11.7 (JCPDS #49-0207).
[0036] Figure 2 The SEM images of Li4Ti5O 0.3 S 11.7 @GO lithium ion sieve are shown. It can be seen that the layered structure of GO still exists, and Li4Ti5O 0.3 S 11.7 nanoparticles appear on the surface, indicating that Li4Ti5O 0.3 S @GO is prepared.In @GO, graphene oxide (GO) serves as the two-dimensional supporting framework, and Li4Ti5O 11.7 S 0.3 Nanoparticles are loaded onto a single layer of graphene oxide.
[0037] Figure 3 H4Ti5O was shown 11.7 S 0.3 @GO and H4Ti5O 12 The water contact angle diagram shows that H4Ti5O 11.7 S 0.3 @GO achieves superhydrophilicity, which may be due to the presence of -OH groups on the GO surface, which enhances the material's hydrophilicity.
[0038] Figure 4 H4Ti5O was shown 11.7 S 0.3 @GO's Ti 4+ Dissolution rate and Li + The elution rate graph shows that H4Ti5O 11.7 S 0.3 @GO after 12 h of pickling treatment, its Li + The elution rate reached 97.7%, Ti 4+ The dissolution rate remained at a low level, approximately 0.87%, indicating that H4Ti5O 11.7 S 0.3 @GO exhibits good structural stability and excellent adsorption performance.
[0039] Example 2
[0040] (1) Lithium ion sieve H4Ti5O 11.9 S 0.1 Preparation of @GO GO powder (0.0387 g) was added to a beaker containing anhydrous ethanol and sonicated for 1 h. Then, anhydrous oxalic acid (1.7 g, 0.019 mol) was added to the system, and stirring continued until dissolved. Next, tetrabutyl titanate (5.74 g, 0.017 mol), lithium acetate dihydrate (1.41 g, 0.021 mol), and lithium sulfide (0.0155 g, 0.00034 mol) were added sequentially to the mixture, with a Ti:S molar ratio of 5:0.1. The mixture was stirred in a magnetic stirrer until completely dissolved, and then 1 ml of deionized water was added. The resulting product was dried in an oven at 80 °C for 48 h, and then calcined in a tube furnace at 750 °C for 3 h under a N2 atmosphere to obtain the precursor Li4Ti5O. 11.9 S 0.1 @GO. Place the precursor in 0.25 mol·L⁻¹ -1acid leaching in HCl solution for 24 h, followed by filtration, washing, and drying in an oven at 50 °C for 12 h, to obtain H4Ti5O 11.9 S 0.1 @GO product.
[0041] (2) Adsorption test Adsorption test and water contact angle measurement were carried out in the same way as in Example 1, and the results are shown in Table 1.
[0042] Figure 5 The obtained precursor Li4Ti5O 11.9 S 0.1 @XRD of GO. According to the XRD pattern, the crystallinity of GO was calculated to be 75%.
[0043] Example 3
[0044] (1) Lithium ion sieve H4Ti5O 11.8 S 0.2 @Preparation of GO The GO (0.0387 g) powder was added to a beaker containing anhydrous ethanol and ultrasonically treated for 1 h. Subsequently, anhydrous oxalic acid (1.7 g, 0.019 mol) was added to the system, and stirring was continued to allow it to dissolve. Then, tetrabutyl titanate (5.74 g, 0.017 mol), lithium acetate dihydrate (1.41 g, 0.021 mol), and lithium sulfide (0.0310 g, 0.00067 mol) were sequentially added to the mixed solution, and the molar ratio of Ti: S in the system was 5: 0.2. The mixture was placed in a magnetic stirrer and stirred until it was completely dissolved, and then 1 ml of deionized water was added. The obtained product was dried in an oven at 80 °C for 48 h, and then calcined in a tube furnace at 750 °C for 3 h under N2 atmosphere to obtain a precursor. The precursor was placed in 0.25 mol·L -1 acid leaching in HCl solution for 24 h, followed by filtration, washing, and drying in an oven at 50 °C for 12 h, to obtain H4Ti5O 11.8 S 0.2 @GO product.
[0045] The obtained precursor Li4Ti5O 11.8 S 0.2 @XRD of GO. According to the XRD pattern, the crystallinity of GO was calculated to be 75%. Figure 5
[0046] (2) Adsorption test Adsorption test and water contact angle measurement were carried out in the same way as in Example 1, and the results are shown in Table 1.
[0047] Example 4
[0048] (1) Lithium ion sieve H4Ti5O 11.6 S 0.4 @Preparation of GO The GO (0.0387 g) powder was added to a beaker containing absolute ethanol and ultrasonically treated for 1 h. Subsequently, oxalic acid (1.7 g, 0.019 mol) was added to the system and stirred to dissolve. Thereafter, tetrabutyl titanate (5.74 g, 0.017 mol), lithium acetate dihydrate (1.41 g, 0.021 mol) and lithium sulfide (0.062 g, 0.00135 mol) were sequentially added to the mixed solution, and the system had a Ti: S molar ratio of 5: 0.4. The mixture was placed in a magnetic stirrer and stirred until completely dissolved, and 1 ml of deionized water was added. The resulting product was dried in an 80 °C oven for 48 h, and then calcined in a tube furnace at 750 °C for 3 h under N2atmosphere to obtain a precursor. The precursor was placed in a 0.25 mol·L -1 HCl solution for 24 h, followed by filtration, washing, and drying in a 50 °C oven for 12 h to obtain H4Ti5O 11.6 S 0.4 @GO product.
[0049] The resulting precursor Li4Ti5O 11.6 S 0.4 @XRD of GO is shown in Figure 5 According to the XRD pattern, the crystallinity was calculated to be 77%.
[0050] (2) Adsorption test The adsorption test and water contact angle measurement were performed in the same manner as in Example 1, and the results are shown in Table 1.
[0051] Example 5
[0052] (1) Lithium ion sieve H4Ti5O 11.5 S 0.5 @Preparation of GO GO (0.0387 g) powder was added to a beaker containing absolute ethanol and sonicated for 1 h. Subsequently, anhydrous oxalic acid (1.7 g, 0.019 mol) was added to the system and stirred to dissolve. Thereafter, tetrabutyl titanate (5.74 g, 0.017 mol), lithium acetate dihydrate (1.41 g, 0.021 mol) and lithium sulfide (0.0775 g, 0.00168 mol) were sequentially added to the mixed solution, and the Ti: S molar ratio in the system was 5: 0.5. The mixture was placed in a magnetic stirrer and stirred until completely dissolved, and 1 ml of deionized water was added. The resulting product was dried in an 80 °C oven for 48 h, and then calcined in a tube furnace at 750 °C for 3 h under N2atmosphere to obtain a precursor. The precursor was placed in 0.25 mol·L -1 HCl solution for 24 h, followed by filtration, washing, and drying in a 50 °C oven for 12 h, to finally obtain H4Ti5O 11.5 S 0.5 @GO product.
[0053] The XRD pattern of the obtained Li4Ti5O 11.5 S 0.5 @GO is shown in FIG. 4. Figure 5 According to the XRD pattern, the crystallinity thereof was calculated to be 73%.
[0054] (2) Adsorption test The adsorption test and water contact angle measurement were performed in the same manner as in Example 1, and the results are shown in Table 1.
[0055] Example 6 (1) Lithium ion sieve H4Ti5O 11.9 S 0.1 @GO-1 GO (0.0387 g) powder was added to a beaker containing absolute ethanol and sonicated for 1 h. Subsequently, anhydrous oxalic acid (1.7 g, 0.019 mol) was added to the system and stirred to dissolve. Thereafter, tetrabutyl titanate (5.74 g, 0.017 mol), lithium acetate dihydrate (1.41 g, 0.021 mol) and thiourea (0.02448 g, 0.00032 mol) were sequentially added to the mixed solution, and the Ti: S molar ratio in the system was 5: 0.1. The mixture was placed in a magnetic stirrer and stirred until completely dissolved, and 1 ml of deionized water was added. The resulting product was dried in an 80 °C oven for 48 h, and then calcined in a tube furnace at 750 °C for 3 h under N2atmosphere to obtain a precursor. The precursor was placed in 0.25 mol·L -1acid leaching in HCl solution for 24 h, followed by filtration, washing, and drying in an oven at 50 °C for 12 h, to obtain H4Ti5O 11.9 S 0.1 @GO-1 product.
[0056] Figure 6 Li4Ti5O 11.9 S 0.1 @XRD pattern of GO-1.
[0057] (2) Adsorption test Adsorption test and water contact angle measurement were carried out in the same manner as in Example 1, and the results are shown in Table 1.
[0058] Example 7 (1) Lithium ion sieve H4Ti5O 11.8 S 0.2 @Preparation of GO-2 GO (0.0387 g) powder was added to a beaker containing absolute ethanol and ultrasonically treated for 1 h. Subsequently, oxalic acid (1.7 g, 0.019 mol) was added to the system, and stirring was continued to allow it to dissolve. Thereafter, tetrabutyl titanate (5.74 g, 0.017 mol), lithium acetate dihydrate (1.41 g, 0.021 mol), and thiourea (0.04896 g, 0.00064 mol) were sequentially added to the mixed solution, and the Ti:S molar ratio in the system was 5:0.2. The mixture was placed in a magnetic stirrer and stirred until it was completely dissolved, and 1 ml of deionized water was further added. The resulting product was dried in an oven at 80 °C for 48 h, and then calcined in a tube furnace at 750 °C for 3 h under N2 atmosphere to obtain a precursor. The precursor was placed in a 0.25 mol·L -1 acid leaching in HCl solution for 24 h, followed by filtration, washing, and drying in an oven at 50 °C for 12 h, to obtain H4Ti5O 11.8 S 0.2 @GO-2 product.
[0059] Figure 6 Li4Ti5O 11.8 S 0.2 @XRD pattern of GO-2.
[0060] (2) Adsorption test Adsorption test and water contact angle measurement were carried out in the same manner as in Example 1, and the results are shown in Table 1.
[0061] Example 8 (1) Lithium ion sieve H4Ti5O 11.7 S 0.3 @Preparation of GO-3 GO (0.0387 g) powder was added to a beaker containing absolute ethanol and sonicated for 1 h. Subsequently, anhydrous oxalic acid (1.7 g, 0.019 mol) was added to the system and stirred to dissolve. Thereafter, tetrabutyl titanate (5.74 g, 0.017 mol), lithium acetate dihydrate (1.41 g, 0.021 mol) and thiourea (0.07344 g, 0.00096 mol) were sequentially added to the mixed solution, with a Ti: S molar ratio of 5: 0.3 in the system. The mixture was placed in a magnetic stirrer to stir until completely dissolved, and 1 ml of deionized water was added. The resulting product was dried in an 80 °C oven for 48 h, and then calcined in a tube furnace at 750 °C for 3 h under N2atmosphere to obtain the precursor. The precursor was placed in 0.25 mol·L -1 HCl solution for 24 h, followed by filtration, washing, and drying in a 50 °C oven for 12 h, to finally obtain H4Ti5O 11.7 S 0.3 @GO-3 product.
[0062] Figure 6 Li4Ti5O 11.7 S 0.3 @GO-3.
[0063] (2) Adsorption test The adsorption test and water contact angle measurement were performed in the same manner as in Example 1, and the results are shown in Table 1.
[0064] Example 9 (1) Lithium ion sieve H4Ti5O 11.6 S 0.4 @GO-4 preparation GO (0.0387 g) powder was added to a beaker containing absolute ethanol and sonicated for 1 h. Subsequently, anhydrous oxalic acid (1.7 g, 0.019 mol) was added to the system and stirred to dissolve. Thereafter, tetrabutyl titanate (5.74 g, 0.017 mol), lithium acetate dihydrate (1.41 g, 0.021 mol) and thiourea (0.09792 g, 0.00128 mol) were sequentially added to the mixed solution, with a Ti: S molar ratio of 5: 0.4 in the system. The mixture was placed in a magnetic stirrer to stir until completely dissolved, and 1 ml of deionized water was added. The resulting product was dried in an 80 °C oven for 48 h, and then calcined in a tube furnace at 750 °C for 3 h under N2atmosphere to obtain the precursor. The precursor was placed in 0.25 mol·L -1acid leaching in HCl solution for 24 h, followed by filtration, washing, and drying in an oven at 50 °C for 12 h, to obtain H4Ti5O 11.6 S 0.4 @GO-4 product.
[0065] Figure 6 Li4Ti5O 11.6 S 0.4 @XRD pattern of GO-4.
[0066] (2) Adsorption test Adsorption test and water contact angle measurement were carried out in the same manner as in Example 1, and the results are shown in Table 1.
[0067] Example 10 (1) Lithium ion sieve H4Ti5O 11.5 S 0.5 @Preparation of GO-5 GO (0.0387 g) powder was added to a beaker containing absolute ethanol and ultrasonically treated for 1 h. Subsequently, oxalic acid (1.7 g, 0.019 mol) was added to the system, and stirring was continued to allow it to dissolve. Thereafter, tetrabutyl titanate (5.74 g, 0.017 mol), lithium acetate dihydrate (1.41 g, 0.021 mol), and thiourea (0.1224 g, 0.0016 mol) were sequentially added to the mixed solution, and the Ti:S molar ratio in the system was 5:0.5. The mixture was placed in a magnetic stirrer and stirred until it was completely dissolved, and 1 ml of deionized water was added. The resulting product was dried in an oven at 80 °C for 48 h, and then calcined in a tube furnace at 750 °C for 3 h under N2atmosphere to obtain a precursor. The precursor was placed in a 0.25 mol·L -1 acid leaching in HCl solution for 24 h, followed by filtration, washing, and drying in an oven at 50 °C for 12 h, to obtain H4Ti5O 11.5 S 0.5 @GO-5 product.
[0068] Figure 6 Li4Ti5O 11.5 S 0.5 @XRD pattern of GO-5.
[0069] (2) Adsorption test Adsorption test and water contact angle measurement were carried out in the same manner as in Example 1, and the results are shown in Table 1.
[0070] Example 11 (1) Lithium ion sieve H4Ti5O 11.9 S 0.1 @Preparation of GO-6 GO (0.0387 g) powder was added to a beaker containing absolute ethanol and sonicated for 1 h. Subsequently, anhydrous oxalic acid (1.7 g, 0.019 mol) was added to the system and stirred to dissolve. Thereafter, tetrabutyl titanate (5.74 g, 0.017 mol), lithium acetate dihydrate (1.41 g, 0.021 mol) and thioacetamide (0.02417 g, 0.00032 mol) were sequentially added to the mixed solution, and the Ti: S molar ratio in the system was 5:0.1. The mixture was stirred in a magnetic stirrer until completely dissolved, and 1 ml of deionized water was added. The resulting product was dried in an 80 °C oven for 48 h, and then calcined in a tube furnace at 750 °C for 3 h under N2atmosphere to obtain a precursor. The precursor was immersed in 0.25 mol·L -1 HCl solution for 24 h, followed by filtration, washing, and drying in a 50 °C oven for 12 h, to finally obtain H4Ti5O 11.9 S 0.1 @GO-6 product.
[0071] Figure 7 H4Ti5O 11.9 S 0.1 XRD pattern of GO-6.
[0072] (2) Adsorption test The adsorption test and water contact angle measurement were performed in the same manner as in Example 1, and the results are shown in Table 1.
[0073] Example 12 (1) Lithium ion sieve H4Ti5O 11.8 S 0.2 Preparation of GO-7 GO (0.0387 g) powder was added to a beaker containing absolute ethanol and sonicated for 1 h. Subsequently, anhydrous oxalic acid (1.7 g, 0.019 mol) was added to the system and stirred to dissolve. Thereafter, tetrabutyl titanate (5.74 g, 0.017 mol), lithium acetate dihydrate (1.41 g, 0.021 mol) and thioacetamide (0.04834 g, 0.00064 mol) were sequentially added to the mixed solution, and the Ti: S molar ratio in the system was 5:0.2. The mixture was stirred in a magnetic stirrer until completely dissolved, and 1 ml of deionized water was added. The resulting product was dried in an 80 °C oven for 48 h, and then calcined in a tube furnace at 750 °C for 3 h under N2atmosphere to obtain a precursor. The precursor was immersed in 0.25 mol·L -1acid leaching in HCl solution for 24 h, followed by filtration, washing, and drying in an oven at 50 °C for 12 h, to obtain H4Ti5O 11.8 S 0.2 @GO-7 product.
[0074] Figure 7 H4Ti5O 11.8 S 0.2 @XRD pattern of GO-7.
[0075] (2) Adsorption test Adsorption test and water contact angle measurement were carried out in the same way as in Example 1, and the results are shown in Table 1.
[0076] Example 13 (1) Lithium ion sieve H4Ti5O 11.7 S 0.3 @Preparation of GO-8 GO (0.0387 g) powder was added to a beaker containing anhydrous ethanol and ultrasonically treated for 1 h. Subsequently, anhydrous oxalic acid (1.7 g, 0.019 mol) was added to the system, and stirring was continued to allow it to dissolve. Then, tetrabutyl titanate (5.74 g, 0.017 mol), lithium acetate dihydrate (1.41 g, 0.021 mol), and thioacetamide (0.07251 g, 0.00096 mol) were sequentially added to the mixed solution, and the Ti: S molar ratio in the system was 5: 0.3. The mixture was placed in a magnetic stirrer and stirred until it was completely dissolved, and 1 ml of deionized water was added. The resulting product was dried in an oven at 80 °C for 48 h, and then calcined in a tube furnace at 750 °C for 3 h under N2 atmosphere to obtain a precursor. The precursor was placed in a 0.25 mol·L -1 acid leaching in HCl solution for 24 h, followed by filtration, washing, and drying in an oven at 50 °C for 12 h, to obtain H4Ti5O 11.7 S 0.3 @GO-8 product.
[0077] Figure 7 Li4Ti5O 11.7 S 0.3 @XRD pattern of GO-8.
[0078] (2) Adsorption test Adsorption test and water contact angle measurement were carried out in the same way as in Example 1, and the results are shown in Table 1.
[0079] Example 14 (1) Lithium ion sieve H4Ti5O 11.6 S 0.4 @Preparation of GO-9 GO (0.0387 g) powder was added to a beaker containing absolute ethanol and sonicated for 1 h. Subsequently, anhydrous oxalic acid (1.7 g, 0.019 mol) was added to the system and stirred to dissolve. Thereafter, tetrabutyl titanate (5.74 g, 0.017 mol), lithium acetate dihydrate (1.41 g, 0.021 mol) and thioacetamide (0.09668 g, 0.00128 mol) were sequentially added to the mixed solution, and the Ti: S molar ratio in the system was 5:0.4. The mixture was stirred in a magnetic stirrer until completely dissolved, and 1 ml of deionized water was added. The resulting product was dried in an 80 °C oven for 48 h, and then calcined in a tube furnace at 750 °C for 3 h under N2atmosphere to obtain a precursor. The precursor was immersed in 0.25 mol·L -1 HCl solution for 24 h, followed by filtration, washing, and drying in a 50 °C oven for 12 h, to finally obtain H4Ti5O 11.6 S 0.4 @GO-9 product.
[0080] Figure 7 H4Ti5O 11.6 S 0.4 XRD pattern of GO-9.
[0081] (2) Adsorption test The adsorption test and water contact angle measurement were performed in the same manner as in Example 1, and the results are shown in Table 1.
[0082] Example 15 (1) Lithium ion sieve H4Ti5O 11.5 S 0.5 Preparation of GO-10 GO (0.0387 g) powder was added to a beaker containing absolute ethanol and sonicated for 1 h. Subsequently, anhydrous oxalic acid (1.7 g, 0.019 mol) was added to the system and stirred to dissolve. Thereafter, tetrabutyl titanate (5.74 g, 0.017 mol), lithium acetate dihydrate (1.41 g, 0.021 mol) and thioacetamide (0.09668 g, 0.00128 mol) were sequentially added to the mixed solution, and the Ti: S molar ratio in the system was 5:0.4. The mixture was stirred in a magnetic stirrer until completely dissolved, and 1 ml of deionized water was added. The resulting product was dried in an 80 °C oven for 48 h, and then calcined in a tube furnace at 750 °C for 3 h under N2atmosphere to obtain a precursor. The precursor was immersed in 0.25 mol·L -1acid leaching for 24 h, followed by filtration, washing, and drying in an oven at 50 °C for 12 h, to obtain H4Ti5O 11.5 S 0.5 @GO-10 product.
[0083] Figure 7 Li4Ti5O 11.5 S 0.5 @XRD pattern of GO-10.
[0084] (2) Adsorption test Adsorption test and water contact angle measurement were performed in the same manner as in Example 1, and the results are shown in Table 1.
[0085] Example 16 Lithium ion sieve H4Ti5O 11.2 S 0.8 @Preparation of GO GO (0.0387 g) powder was added to a beaker containing anhydrous ethanol and ultrasonically treated for 1 h. Subsequently, anhydrous oxalic acid (1.7 g, 0.019 mol) was added to the system, and stirring was continued to allow it to dissolve. Thereafter, tetrabutyl titanate (5.74 g, 0.017 mol), lithium acetate dihydrate (1.41 g, 0.021 mol), and lithium sulfide (0.124 g, 0.0027 mol) were sequentially added to the mixed solution, and the Ti:S molar ratio in the system was 5:0.8. The mixture was placed in a magnetic stirrer and stirred until it was completely dissolved, and 1 ml of deionized water was further added. The resulting product was dried in an oven at 80 °C for 48 h, and then calcined in a tube furnace at 750 °C for 3 h under N2atmosphere to obtain a precursor. The precursor was subjected to acid leaching in a 0.25 mol / L HCl solution for 24 h, followed by filtration, washing, and drying in an oven at 50 °C for 12 h, to obtain H4Ti5O 11.2 S 0.8 @GO product.
[0086] Example 17 Lithium ion sieve H4Ti5O 11.2 S 0.8 @Preparation of GO-11 GO (0.0387 g) powder was added to a beaker containing absolute ethanol and sonicated for 1 h. Subsequently, anhydrous oxalic acid (1.7 g, 0.019 mol) was added to the system and stirred to dissolve. Thereafter, tetrabutyl titanate (5.74 g, 0.017 mol), lithium acetate dihydrate (1.41 g, 0.021 mol), and thiourea (0.196 g, 0.0027 mol) were sequentially added to the mixed solution, and the Ti: S molar ratio in the system was 5:0.8. The mixture was stirred in a magnetic stirrer until complete dissolution, and 1 ml of deionized water was added. The resulting product was dried in an 80 °C oven for 48 h, and then calcined in a tube furnace under N2atmosphere at 750 °C for 3 h to obtain a precursor. The precursor was immersed in 0.25 mol·L -1 HCl solution for 24 h, followed by filtration, washing, and drying in a 50 °C oven for 12 h to obtain H4Ti5O 11.2 S 0.8 @GO-11 product.
[0087] Example 18 Lithium ion sieve H4Ti5O 11.2 S 0.8 Preparation of GO-12 GO (0.0387 g) powder was added to a beaker containing absolute ethanol and sonicated for 1 h. Subsequently, anhydrous oxalic acid (1.7 g, 0.019 mol) was added to the system and stirred to dissolve. Thereafter, tetrabutyl titanate (5.74 g, 0.017 mol), lithium acetate dihydrate (1.41 g, 0.021 mol), and thioacetamide (0.193 g, 0.0027 mol) were sequentially added to the mixed solution, and the Ti: S molar ratio in the system was 5:0.8. The mixture was stirred in a magnetic stirrer until complete dissolution, and 1 ml of deionized water was added. The resulting product was dried in an 80 °C oven for 48 h, and then calcined in a tube furnace under N2atmosphere at 750 °C for 3 h to obtain a precursor. The precursor was immersed in 0.25 mol·L -1 HCl solution for 24 h, followed by filtration, washing, and drying in a 50 °C oven for 12 h to obtain H4Ti5O 11.2 S 0.8 @GO-12 product.
[0088] Comparative Example 19 (1) Lithium ion sieve H4Ti5O 12 Preparation of GO-13 (Li4Ti5O 12 :GO mass ratio 1:0.025) GO (0.0387 g) powder was added to a beaker containing absolute ethanol and sonicated for 1 h. Subsequently, anhydrous oxalic acid (1.7 g, 0.019 mol) was added to the system and stirred to dissolve. Thereafter, tetrabutyl titanate (5.74 g, 0.017 mol) and lithium acetate dihydrate (1.41 g, 0.021 mol) were added to the mixed solution in sequence, and the system had a Li:Ti molar ratio of 4:5. The mixture was placed in a magnetic stirrer and stirred until completely dissolved, and 1 ml of deionized water was added. The resulting product was dried in an 80 °C oven for 48 h, and then calcined in a tube furnace at 750 °C for 3 h under N2atmosphere to obtain a precursor. The precursor was immersed in 0.25 mol·L -1 HCl solution for 24 h, followed by filtration, washing, and drying in a 50 °C oven for 12 h to obtain H4Ti5O 12 @GO-13 product.
[0089] (2) Adsorption test The adsorption test and water contact angle measurement were performed in the same manner as in Example 1, and the results are shown in Table 1.
[0090] Example 20 (1) Lithium ion sieve H4Ti5O 11.7 S 0.3 @Preparation of GO-14 GO (0.0387 g) powder was added to a beaker containing absolute ethanol and sonicated for 1 h. Subsequently, anhydrous oxalic acid (1.7 g, 0.019 mol) was added to the system and stirred to dissolve. Thereafter, tetrabutyl titanate (5.74 g, 0.017 mol), lithium acetate dihydrate (1.41 g, 0.021 mol), and lithium sulfide (0.047 g, 0.0010 mol) were added to the mixed solution in sequence, and the system had a Ti:S molar ratio of 5:0.3. The mixture was placed in a magnetic stirrer and stirred until completely dissolved, and 1 ml of deionized water was added. The resulting product was dried in an 80 °C oven for 48 h, and then calcined in a tube furnace at 650 °C for 5 h under N2atmosphere to obtain a precursor. The precursor was immersed in 0.25 mol·L -1 HCl solution for 24 h, followed by filtration, washing, and drying in a 50 °C oven for 12 h to obtain H4Ti5O 11.7 S 0.3 @GO-14 product.
[0091] (2) Adsorption test The adsorption test and water contact angle measurement were performed in the same manner as in Example 1, and the results are shown in Table 1.
[0092] Example 21 (1) Lithium ion sieve H4Ti5O 11.7 S 0.3 Preparation of GO-15 GO (0.0387 g) powder was added to a beaker containing absolute ethanol and sonicated for 1 h. Subsequently, anhydrous oxalic acid (1.7 g, 0.019 mol) was added to the system and stirred to dissolve. Thereafter, tetrabutyl titanate (5.74 g, 0.017 mol), lithium acetate dihydrate (1.41 g, 0.021 mol), and lithium sulfide (0.047 g, 0.0010 mol) were sequentially added to the mixed solution, and the Ti: S molar ratio in the system was 5:0.3. The mixture was stirred in a magnetic stirrer until completely dissolved, and 1 ml of deionized water was added. The resulting product was dried in an 80 °C oven for 48 h, and then calcined in a tube furnace at 850 °C for 2 h under N2atmosphere to obtain a precursor. The precursor was immersed in a 0.25 mol·L -1 HCl solution for 24 h, followed by filtration, washing, and drying in a 50 °C oven for 12 h to obtain H4Ti5O 11.7 S 0.3 GO-15 product.
[0093] (2) Adsorption test The adsorption test and water contact angle measurement were performed in the same manner as in Example 1, and the results are shown in Table 1.
[0094] Example 22 Lithium ion sieve H4Ti5O 11.7 S 0.3 Preparation of GO-16 (Li4Ti5O 12 : mass ratio of GO 1:0.0125) GO (0.0193 g) powder was added to a beaker containing absolute ethanol and sonicated for 1 h. Subsequently, anhydrous oxalic acid (1.7 g, 0.019 mol) was added to the system and stirred to dissolve. Thereafter, tetraisopropyl titanate (4.83 g, 0.017 mol), lithium hydroxide (0.50 g, 0.021 mol), and lithium sulfide (0.047 g, 0.0010 mol) were sequentially added to the mixed solution, and the Ti: S molar ratio was 5:0.3. The mixture was stirred in a magnetic stirrer until completely dissolved, and 1 ml of deionized water was added. The resulting product was dried in an 80 °C oven for 48 h, and then calcined in a tube furnace at 750 °C for 3 h under N2atmosphere to obtain a precursor. The precursor was immersed in a 0.25 mol·L -1acid leaching in HCl solution for 24 h, followed by filtration, washing, and drying in an oven at 50 °C for 12 h, to obtain H4Ti5O 11.7 S 0.3 GO-16 product.
[0095] Example 23 lithium ion sieve H4Ti5O 11.7 S 0.3 Preparation of GO-17 (Li4Ti5O 12 mass ratio of GO to Li2CO3 1:0.05) GO (0.0774 g) powder was added to a beaker containing absolute ethanol and sonicated for 1 h. Subsequently, oxalic acid (1.7 g, 0.019 mol) was added to the system and stirred to dissolve. Then, titanium chloride (3.23 g, 0.017 mol), lithium carbonate (1.55 g, 0.021 mol), and lithium sulfide (0.047 g, 0.0010 mol) were added to the mixed solution in sequence, and the molar ratio of Li:Ti in the system was 4:5. The mixture was stirred in a magnetic stirrer until it was completely dissolved, and 1 ml of deionized water was added. The resulting product was dried in an oven at 80 °C for 48 h, and then calcined in a tube furnace at 750 °C for 3 h under N2 atmosphere to obtain a precursor. The precursor was placed in 0.25 mol·L -1 acid leaching in HCl solution for 24 h, followed by filtration, washing, and drying in an oven at 50 °C for 12 h, to obtain H4Ti5O 11.7 S 0.3 GO-17 product.
[0096] Application Example
[0097] The prepared composite lithium ion sieve was evaluated for its adsorption capacity Q t , equilibrium adsorption time T, and adsorption selectivity in salt lake brine. H4Ti5O 12 GO was used as a comparison, and was compared with Li4Ti5O 11.7 S 0.3 and H4Ti5O 12 in Comparative Example 19.
[0098] (1) Adsorption capacity Q t and adsorption equilibrium time T test: 1 g of the lithium ion sieve prepared in Examples 1-15 and 19-21 was added to 1 L of LiOH solution (100 mg·L -1The solution was stirred and adsorption tests were conducted. The concentration of Li in the solution was measured using ICP (inductively coupled plasma). + The initial concentration (C0) and instantaneous concentration (C) t (This continues until adsorption equilibrium is reached.) Lithium ion sieve or H4Ti5O 12 @GO's adsorption capacity Q t It is calculated using formula (2).
[0099] (2) Where: C t Take the concentration value at adsorption equilibrium, mg·L -1 ; V represents the solution volume, in L; m represents the mass of the lithium-ion sieve, in grams.
[0100] (2) Adsorption cycle test (calculated based on an 80% decrease in adsorption capacity): 1 g lithium ion sieve or H4Ti5O 12 @GO in LiOH solution (100 mg·L) -1 The cycling performance in the process was assessed using a lithium-ion sieve or H4Ti5O after adsorption. 12 @GO after 0.25 mol mg·L -1 After HCl washing, the adsorption experiment was repeated, and the adsorption capacity was measured after each cycle until the adsorption capacity decreased to 80% of the initial value, and the number of cycles was obtained. The test method conditions and calculation formula are the same as formula (2).
[0101] (3) Adsorption selectivity test (using Li) + For Mg 2+ (The separating factor is the object of study): At 25 °C, 1 g of lithium-ion sieve or H4Ti5O was used. 12 @GO placed in a solution containing Li at pH = 8 + Na + Ca 2+ K + and Mg 2+ The concentrations of ions in the salt lake brine were 73.23, 232.8, 169.5, 299.3, and 337.6 mg·L⁻¹, respectively. -1 After 24 h of adsorption, the adsorption selectivity of the lithium ion sieve was determined. The concentration of Li in the solution was measured using ICP. + The initial concentration (C0) and instantaneous concentration (C) of the hetero ions at adsorption time t t ). With heteroions Mg 2+ For example, the allocation coefficient (K) d) and separation factor ( ) are calculated by formula (3) and (4) respectively.
[0102] (3) (4) Wherein: K d is distribution coefficient, mL·g -1 ; V is the volume of solution, L; m is the mass of lithium ion sieve sample, g; C e is the concentration of remaining ions in the solution, mg·g -1 .
[0103] The experimental results are shown in Table 1.
[0104] Table 1
[0105] It can be seen that the composite lithium ion sieve has high adsorption capacity, good structural stability, excellent hydrophilicity, and especially high selective adsorption capacity for high magnesium-lithium ratio salt lake brine, and is suitable for selective adsorption and extraction of lithium ions from low-concentration geothermal water, battery waste liquid, salt lake brine and seawater and other complex water bodies, and is a reusable high-efficiency lithium ion adsorption material.
Claims
1. A sulfur-doped metatitanic acid / graphene oxide two-dimensional composite lithium ion sieve, characterized in that, The active component is the precursor Li4Ti5O 12-x S x The delithiation product H4Ti5O 12-x S x Graphene oxide serves as the carrier, and the active component is H4Ti5O. 12-x S x Nanoparticles loaded on a single layer of graphene oxide, denoted as H4Ti5O 12-x S x @GO; where x = 0.05 - 0.
8.
2. The sulfur-doped metatitanic acid / graphene oxide two-dimensional composite lithium ion sieve according to claim 1, characterized in that, The x is 0.1-0.
5.
3. The sulfur-doped metatitanic acid / graphene oxide two-dimensional composite lithium ion sieve according to claim 1, characterized in that, The active component is Li4Ti5O 12 with the mass ratio of Li4Ti5O 12 : graphene oxide = 1 : (0.0125~0.05).
4. The H4Ti5O 12-x S x @Preparation method of GO lithium ion sieve, comprising the following steps: uniformly dispersing graphene oxide powder in ethanol by ultrasonic dispersion, adjusting the pH of the solution to 2-3, then adding a titanium source, a lithium source and a sulfur source, stirring and dissolving to obtain a mixed solution, adding deionized water, drying the obtained product, and calcining in a N2 atmosphere to obtain a precursor; acid leaching the obtained precursor in an acid solution to remove lithium, filtering, washing and drying to obtain H4Ti5O 12-x S x @GO lithium ion sieve.
5. The H4Ti5O 12-x S x @Process for the preparation of a lithium ion sieve of the type GO, characterized in that, The titanium source is selected from tetrabutyl titanate, tetraisopropyl titanate, titanium acetate, titanium nitrate, titanium sulfate or titanium chloride.
6. The H4Ti5O 12-x S x @Process for the preparation of a lithium ion sieve of the type GO, characterized in that, The lithium source is selected from lithium acetate, lithium nitrate, lithium hydroxide or lithium carbonate, or a hydrate thereof.
7. The H4Ti5O 12-x S x @Process for the preparation of a lithium ion sieve of the type GO, characterized in that, The sulfur source is selected from lithium sulfide, thiourea, thioacetamide, titanium disulfide or sulfur.
8. The H4Ti5O 12-x S x @Process for the preparation of a lithium ion sieve of the type GO, characterized in that, In the mixed solution, Li4Ti5O 12 Calculation, Li4Ti5O 12 The mass ratio of GO is 1: (0.0125~0.05).
9. The H4Ti5O 12-x S x @Process for the preparation of a lithium ion sieve of the type GO, characterized in that, The molar ratio of Ti:S in the mixed solution is 5:x, x=0.05-0.
8.
10. The H4Ti5O 12-x S x @Process for the preparation of a lithium ion sieve of the type GO, characterized in that, The calcination temperature is 650 ℃-850 ℃, and the calcination time is 2-5 h.